Strengthening Indigenous Governance Structures based on Local Wisdom in Protecting the Territorial Rights of Indigenous Peoples - Asnat Juljana Luturmas; Lita Tyesta Addy Listya Wardhani; Sukirno Sukirno (Riviera Publishing, 2024)
The purpose of this research is to provide strengthening of indigenous governance structures based on local wisdom in protecting the territorial rights of Indigenous Peoples. The research method can be grouped into the realm of socio-legal research, namely the type of socio-legal research, so the approach used is the non-doctrinal approach method. The results show that the strengthening of indigenous government structures based on local wisdom has been implemented in the Republic of Indonesia and has received protection guarantees, but the regulation of the existence of indigenous government structures in strengthening the territorial rights of indigenous peoples has not been answered properly. Recognition of smaller community unit areas cannot only be guaranteed by using policies alone, the existence of indigenous government structures in villages / customary territories / other names is not just formed but is influenced by genelogical-territorial so that regional ties and blood descent structures are very strong. Legal requirements Article 97 Paragraphs (1) and (2) of the Village Law explain that the establishment of an adat village must fulfill the following requirements: the existence of a customary law community unit along with its traditional rights that are actually still alive, whether territorial, genelogical, or functional in nature and the existence of customary government institutions. The implications of this research suggest that for the effective protection of Indigenous Peoples' territorial rights, a more comprehensive legal and policy framework is needed that recognizes and supports the complex genealogical and territorial structures of customary governance.